Drivers of Cross-Border Banking in Sub-Saharan Africa - Mathieu, Paul (IMF Working Papers; Working Paper ;, 2019)
Using data collected from pan-African banks' (PABs), balance sheets and other sources (Orbis, Fitch), this study identifies some key patterns of cross-border investment in bank subsidiaries by key banking groups in sub-Saharan Africa (SSA) and discusses some of the determinants of this investment. Using a gravity model relating the annual value of a banking group's investment in the net equity of its subsidiaries to a set of explanatory variables, the analysis finds that cross-border banking is in part driven by a search for yield, diversification, and expansion for strategic reasons.